2019
DOI: 10.1007/s00431-018-3306-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of the family of children with asthma is not related to asthma severity

Abstract: The quality of life for the family is an important outcome of childhood asthma. The aim of the study was to describe the quality of life in Eastern European families who have a child with asthma. The Pediatric Quality of Life Inventory Family Impact Module was completed by the parents of 527 children with asthma. The median overall score was 75.0 (Interquartile range 63.9; 87.5). The following factors were independently associated with lower quality of life: waking with asthma symptoms ≥one night a week (odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 25 publications
0
21
1
3
Order By: Relevance
“…The total PedsQL™ FIM and parental HRQoL of caregivers of children with CKD was lower in our population compared with other studies of caregivers of children with other chronic diseases (asthma [ 26 ], osteogenesis imperfecta [ 27 ], sickle cell disease [ 8 ], asthma and heart diseases [ 3 ], chronic gastrointestinal disorders [ 2 ], chronic pain [ 7 ], nephrotic syndrome [ 28 ], disabilities [ 29 ], and different chronic conditions [ 15 ]).…”
Section: Discussioncontrasting
confidence: 76%
“…The total PedsQL™ FIM and parental HRQoL of caregivers of children with CKD was lower in our population compared with other studies of caregivers of children with other chronic diseases (asthma [ 26 ], osteogenesis imperfecta [ 27 ], sickle cell disease [ 8 ], asthma and heart diseases [ 3 ], chronic gastrointestinal disorders [ 2 ], chronic pain [ 7 ], nephrotic syndrome [ 28 ], disabilities [ 29 ], and different chronic conditions [ 15 ]).…”
Section: Discussioncontrasting
confidence: 76%
“…Asthma control is probably the most valuable determinant of HRQoL whatever the level of disease severity is. [32][33][34] Nevertheless, a proportion of our asthmatic children (13%) reported no problems in all the 5 dimensions. This was previously reported by Bergfors et al who used the PAQLQ in addition to the EQ-5D-Y and found that 50% of their asthma children had a health profile of 11111 denoting no problem.…”
Section: Discussionmentioning
confidence: 72%
“…Depression is a negative emotion with mutual transfer phenomenon, and the transfer phenomenon of depression can be strong and rapid in relationships in which daily stress is experienced in the same space where parents raise children [19]. In particular, because parents of asthmatic children have greater psychological burden of performing many roles as parents since they continuously experience the disease process and growth of children at the same time [4], the transfer phenomenon of parental depression is strong and fast and ultimately becomes the cause of marital conflict and negatively influences the growth and development process, resulting in problem behavior and affecting academic performance of children. Since this study found that maternal depression has a direct influence on children's internalizing and externalizing problem behavior, the effect of maternal depression on children appears to be greater than that of paternal depression.…”
Section: Discussionmentioning
confidence: 99%
“…The health issues of children with asthma is emerging to be a social problem because in many cases it is a disease that requires repetitive and long-term treatment, and the financial burden of parents raising children with asthma is relatively greater than parents raising normal children [3]. Furthermore, parents of asthmatic children have the greater psychological burden of performing many roles since they experience the disease process and growth of their children at the same time [4].…”
Section: Introductionmentioning
confidence: 99%